The uncompleted privatization of functional land in Slovenia and attempts at its renationalization - Vlahek Ana; Damjan Matija (Anali Pravnog Fakulteta u Beogradu)
The article discusses the unsettled ownership status of many tracts of urban land in Slovenian cities that persists as a consequence of the disorderly transition from the socialist into the market institutional environment. Problems arising from the privatization of real estate, which can be detected all over the former Yugoslavia, typically affect functional land, i.e. land directly intended for the regular use and functioning of a building. Frequently, the land register does not show the rightful ownership status of such plots, leading to disputes and lengthy court proceedings for the determination of ownership. This is particularly the case with shared outdoor parts of residential neighborhoods, which are often subject to unfounded ownership claims based on obsolete entries in the land register. Even some municipal authorities have attempted to bring such land into public domain under this pretense, which would, if successful, amount to a 21st century nationalization.